Word Forming Features of English Terms in the field of Copyright - Mavutova , Shakhlo (The Lingua Spectrum, 2025)
This article analyzes the word formation features of English terms in the field of copyright. It explores the morphological and semantic structure of copyright-related terminology, focusing on various word-formation methods such as, affixation, compounding, abbreviation, conversion. These mechanisms play a vital role in shaping precise legal language that is both functional and adaptable. The article includes numerous examples from legal texts, international agreements, and copyright law documents to support its analysis. It also highlights challenges faced in translating such terms accurately into other languages due to their specialized and context-dependent meanings. Moreover, the research discusses the importance of copyright terms in facilitating international legal communication and standardization. Understanding how these terms are formed contributes to better comprehension and more effective use of legal English in multilingual contexts. This study will be particularly valuable for linguists, legal translators, educators, and legal professionals working with English legal discourse and terminology.